Masyarakat Madura Perantauan dan Pandemi Covid-19: Uji Model Kepatuhan Protocol Covid-19 melalui Persepsi Resiko Covid-19, Kepercayaan Warga Negara, Locus of Control dan Sikap Anti terhadap Vaksin - Lusy Asa Akhrani; Bintari Ratih Kusumaningrum; Ida Puji Lestari; Emy Sudarwati (Universitas Andalas, 2022)
As Covid-19 cases soared in Indonesia, various efforts have been made by the government to overcome the spike in cases. This study aimed to examine the model of compliance with the Covid-19 protocol for migrant Madurese through perceived risk of Covid-19, citizen trust, locus of control, and anti-vaccine attitudes. A total of 245 migrant Madurese community were recruited by purposive sampling. The results showed that the theoretical model of compliance with the Covid-19 protocol was built through Citizen Trust, Locus of Control, and Anti-Vaccine Attitudes, while risk perception as a moderating variable had no effect on the compliance with the Covid-19 protocol. The results also showed that risk perception did not have a significant effect on the compliance with the Covid-19 protocol, but risk perception was influenced by citizen trust and anti-vaccine attitudes. Citizen compliance and anti-vaccine attitudes only had a direct effect on compliance with the Covid-19 protocol without any mediating variables.